Somatosensory Processing of the Tongue in Humans - Sakamoto, Kiwako; Nakata, Hiroki; Yumoto, Masato; Kakigi, Ryusuke (Frontiers in Physiology, 2010)
We review research on somatosensory (tactile) processing of the tongue based on data obtained using non-invasive neurophysiological and neuroimaging methods. Technical difficulties in stimulating the tongue, due to the noise elicited by the stimulator, the fixation of the stimulator, and the vomiting reflex, have necessitated the development of specialized devices. In this article, we show the brain activity relating to somatosensory processing of the tongue evoked by such devices. More recently, the postero-lateral part of the tongue has been stimulated, and the brain response compared with that on stimulation of the antero-lateral part of the tongue. It is likely that a difference existed in somatosensory processing of the tongue, particularly around primary somatosensory cortex (SI), Brodmann area 40 (BA 40), and the anterior cingulate cortex (ACC).